Research Ideas on Education in Karakalpak stan During the Years of Independence - Y.E. Purhanov (Genius Journals, 2022)
The article discusses the development of pedagogical science in Karakalpakstan during the years of independence and the research work of pedagogical scientists, as well as the importance of pedagogical ideas in educating young people
Keywords: Pedagogy; educational education; person; integration